RNA neoantigen vaccines prime long-lived CD8+ T cells in pancreatic cancer - Sethna, Zachary; Guasp, Pablo; Reiche, Charlotte; Milighetti, Martina; Ceglia, Nicholas; Patterson, Erin; Lihm, Jayon; Payne, George; Lyudovyk, Olga; Rojas, Luis A.; Pang, Nan; Ohmoto, Akihiro; et al. (Nature (London), 2025)
A fundamental challenge for cancer vaccines is to generate long-lived functional T cells that are specific for tumour antigens. Here we find that mRNA–lipoplex vaccines against somatic mutation-derived neoantigens may solve this challenge in pancreatic ductal adenocarcinoma (PDAC), a lethal cancer with few mutations. At an extended 3.2-year median follow-up from a phase 1 trial of surgery, atezolizumab (PD-L1 inhibitory antibody), autogene cevumeran 1 (individualized neoantigen vaccine with backbone-optimized uridine mRNA–lipoplex nanoparticles) and modified (m) FOLFIRINOX (chemotherapy) in patients with PDAC, we find that responders with vaccine-induced T cells ( n = 8) have prolonged recurrence-free survival (RFS; median not reached) compared with non-responders without vaccine-induced T cells ( n = 8; median RFS 13.4 months; P =  0.007). In responders, autogene cevumeran induces CD8 + T cell clones with an average estimated lifespan of 7.7 years (range 1.5 to roughly 100 years), with approximately 20% of clones having latent multi-decade lifespans that may outlive hosts. Eighty-six percent of clones per patient persist at substantial frequencies approximately 3 years post-vaccination, including clones with high avidity to PDAC neoepitopes. Using PhenoTrack, a novel computational strategy to trace single T cell phenotypes, we uncover that vaccine-induced clones are undetectable in pre-vaccination tissues, and assume a cytotoxic, tissue-resident memory-like T cell state up to three years post-vaccination with preserved neoantigen-specific effector function. Two responders recurred and evidenced fewer vaccine-induced T cells. Furthermore, recurrent PDACs were pruned of vaccine-targeted cancer clones. Thus, in PDAC, autogene cevumeran induces de novo CD8 + T cells with multiyear longevity, substantial magnitude and durable effector functions that may delay PDAC recurrence. Adjuvant mRNA–lipoplex neoantigen vaccines may thus solve a pivotal obstacle for cancer vaccination. In a phase 1 trial, patients with pancreatic ductal adenocarcinoma who were treated with surgery and bespoke neoantigen mRNA vaccines combined with anti-PD-L1 and chemotherapy exhibited marked long-lived persistence of neoantigen-specific CD8 + T cell clones, which correlated with prolonged recurrence-free survival at a 3.2-year follow-up.